Integrating spirituality into multicultural counseling - Fukuyama, Mary A.; Sevig, Todd D.; Sage eBooks (Thousand Oaks, Calif. ; London : SAGE, 1999)
Challenging practitioners, Fukuyama and Sevig propose that integrating spiritual values in multicultural counselling and exploring spirituality from multicultural perspectives are mutually beneficial processes.
Specialized.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Cross-cultural counseling; Spirituality; Cultural pluralism; Transpersonal psychology; Religion and culture; Electronic books